- 1-800-665-6601
- [email protected]

We can convert the given equation into y = mx + b.

To do that, first we can shift the 3x to the right hand side of the equality.

Then we have 2y = - 3x + 6

Now we can divide this equation by 2

Then we have the equation y = (-3/ 2) x + 3

Here, y intercept = b = 3

We can convert the given equation into (x/a) + (y/b) = 1

Here b is the y intercept

To convert into this form, first we can divide this equation by 15

Then we have (3x/15) + (5y/15) = 1

We can write above equation as (x/ 5) + (y/3) = 1

Here, y intercept = b = 3.